2017
DOI: 10.1371/journal.pone.0173557
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of muscle disease in the canine model of Duchenne muscular dystrophy by electrical impedance myography

Abstract: Dystrophin-deficient dogs are by far the best available large animal models for Duchenne muscular dystrophy (DMD), the most common lethal childhood muscle degenerative disease. The use of the canine DMD model in basic disease mechanism research and translational studies will be greatly enhanced with the development of reliable outcome measures. Electrical impedance myography (EIM) is a non-invasive painless procedure that provides quantitative data relating to muscle composition and histology. EIM has been ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Electrical impedance myography is another method for measuring intrinsic muscle properties and has been utilized as a pre-clinical and clinical non-invasive biomarker in numerous settings of muscle disease. Hakim et al (2017) showed that EIM was able to measure significant difference in EIM parameters in DMD canines that significantly correlated with fibrotic build-up in the measured muscles. EIM has also been utilized in multiple clinical settings in FSHD (Rutkove et al, 2007;Mul et al, 2018), ALS (Rutkove et al, 2007, and DMD where it was also shown to be responsive to intervention with corticosteroids.…”
Section: Non-invasive Biomarkers For Fibrosismentioning
confidence: 93%
“…Electrical impedance myography is another method for measuring intrinsic muscle properties and has been utilized as a pre-clinical and clinical non-invasive biomarker in numerous settings of muscle disease. Hakim et al (2017) showed that EIM was able to measure significant difference in EIM parameters in DMD canines that significantly correlated with fibrotic build-up in the measured muscles. EIM has also been utilized in multiple clinical settings in FSHD (Rutkove et al, 2007;Mul et al, 2018), ALS (Rutkove et al, 2007, and DMD where it was also shown to be responsive to intervention with corticosteroids.…”
Section: Non-invasive Biomarkers For Fibrosismentioning
confidence: 93%
“…EIM has also been applied in various animal studies as models of human disease; mice (Li et al 2012), rats (Ahad and Rutkove 2009), and dogs (Hakim et al 2017) have been measured using adhesive electrodes, surface metal electrodes, and needle electrodes. The specifics of which electrode is used depends on the size of the animal, the presence of fur, and the specific questions of interest.…”
Section: Overview Of the Clinical Application Of Electrical Impedance Myography In Neuromuscular Disorders Eim Methods And Applicationsmentioning
confidence: 99%
“…Previous studies have also investigated relationships between impedance values and cell size and connective tissue deposition. In preclinical studies of the mdx mouse model, 25,46–48 as well as in a canine model of DMD, 49 we demonstrated a significant correlation between EIM values and HP tissue content. However, impedance values have not been used previously to predict morphological features of dystrophic muscle, such as myofiber size or fibrosis.…”
Section: Discussionmentioning
confidence: 59%